Association between neuropathic pain and A-Waves in Leprosy patients with type 1 and 2 reactions - Garbino, José A.; Naafs, Bernard; Salgado, Manoel Henrique [UNESP]; Ura, Somei; Virmond, Marcos da C. L.; Schestatsky, Pedro (Wolters Kluwer, 2011)
Summary: Neuropathic pain (NP) is a well-recognized feature of leprosy neuropathy. However, the diagnosis of NP is difficult using only clinical criteria. In the study reported here, by means of conventional nerve conduction studies, the authors sought for an association between long-latency responses and NP complaints in leprosy patients with type 1 and 2 reactions. Of the 27 ulnar nerves of leprosy patients, 18 with type 1 reaction (T1R) and 9 with type 2 reaction (T2R) were followed-up for 6 months before and after steroid treatment. Clinical characteristics of pain complaints and clinical function were assessed, as well as the presence of F- and A-waves of the ulnar nerve using nerve conduction studies. The clinical and the neurophysiologic findings were compared to note positive concordances (presence of NP and A-waves together) and negative concordances (absence of NP and A-waves together) before and after treatment. Both reactions presented a high frequency of A-waves (61.1% in T1R and 66.7% in T2R, P < 0.05) and prolonged F-waves (69.4% in T1R and 65.8% in T2R, P = 0.4). No concordances were seen between pain complaints and F-waves. However, significant concordances between NP and A-waves were observed, although restricted to the T2R group ([chi]2 = 5.65, P = 0.04). After treatment, there was a significant reduction in pain complaints, as well as the presence of F- and A-waves in both groups (P < 0.05 for all comparisons). In conclusion, the presence of A-waves correlates well with pain complaints of neuropathic characteristics in leprosy patients, especially in those with type 2 reaction. Probably, such response shares similar mechanisms with the small-fiber dysfunction seen in these patients with NP, such as demyelination, intraneural edema, and axonal sprouting. Further studies using specific tools for small-fiber assessment are warranted to confirm our findings.